Layered Metal Composites as a Promising Class of Modern Materials - M.A. Latypova, B.B. Makhmutov, and A.S. Yerzhanov (Успехи физики металлов)
The intensive development of the transport, chemical, atomic power engineering, shipbuilding, and aerospace engineering necessitates the creation of new materials with a unique set of physical-mechanical and functional properties. Such materials include an extensive group of layered metal composite materials based on dissimilar and heterogeneous metals and alloys, which, due to the presence of laminated and sandwich structures, allow to obtain a complex of difficult-to-combine properties: high strength, ductility, toughness at low-climatic and cryogenic temperatures, wear resistance, thermal and electrical conductivities. One of the current directions of modern materials science is the development of layered metal composite materials for multifunctional purposes with layers of consolidated mixtures of Al powders and reinforcing particles Al2O3, SiC, and B4C, which can be used for the fabrication of products and structures with specified tribological and thermophysical characteristics, high ballistic resistance, as well as for the manufacturing of radiation protective elements of the nuclear or space engineering.